Threat and Prejudice against Central American Undocumented Migration in Mexico - Buenrostro Mercado, Diana; Ramos Lira, Luciana (Nómadas, 2021)
The article seeks to determine, in inhabitants of the Metropolitan Area of the Valley of Mexico, if there is an association between the perception of threat (realistic or symbolic) and the expression of prejudice (subtle or overt) against Central American migrants in transit. The article explains how age, schooling, and the assessment of previous contact with migrants, are important factors in this link. The authors conclude by proposing spaces for education or the promotion of tolerance and encounters between Mexicans and migrants, to encourage interaction in order to reduce the levels of perception of threat and expressions of prejudice.